2010
DOI: 10.1155/2010/718142
|View full text |Cite
|
Sign up to set email alerts
|

Correctness of Protein Identifications ofBacillus subtilisProteome with the Indication on Potential False Positive Peptides Supported by Predictions of Their Retention Times

Abstract: The predictive capability of the retention time prediction model based on quantitative structure-retention relationships (QSRR) was tested. QSRR model was derived with the use of set of peptides identified with the highest scores and originated from 8 known proteins annotated as model ones. The predictive ability of the QSRR model was verified with the use of a Bacillus subtilis proteome digest after separation and identification of the peptides by LC-ESI-MS/MS. That ability was tested with three sets of testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In summary, progress in mass spectrometry allows the masses of biomolecular ions to be measured with sub-ppm precision; however, this accuracy is still far from being sequence-specific for peptides, which is the deficiency countered by MS/MS . Numerous studies have shown that retention times are sequence-specific in the case of peptides and proteins and may potentially replace MS/MS. This intrinsic value of the chromatography data was also extensively explored, mainly to support peptide identification and validation by reducing the search space or helping the identification of the features in MS1 spectra. , One of the main obstacles associated with the use of chromatography for implementing true MS1-based proteomics workflows is its relatively low accuracy in the prediction of retention times for peptides, which is still much lower compared with LC’s experimental precision and reproducibility . In other words, exact masses measured with sub-ppm accuracy and retention times alone were not enough to identify a tryptic peptide from a database unambiguously.…”
mentioning
confidence: 99%
“…In summary, progress in mass spectrometry allows the masses of biomolecular ions to be measured with sub-ppm precision; however, this accuracy is still far from being sequence-specific for peptides, which is the deficiency countered by MS/MS . Numerous studies have shown that retention times are sequence-specific in the case of peptides and proteins and may potentially replace MS/MS. This intrinsic value of the chromatography data was also extensively explored, mainly to support peptide identification and validation by reducing the search space or helping the identification of the features in MS1 spectra. , One of the main obstacles associated with the use of chromatography for implementing true MS1-based proteomics workflows is its relatively low accuracy in the prediction of retention times for peptides, which is still much lower compared with LC’s experimental precision and reproducibility . In other words, exact masses measured with sub-ppm accuracy and retention times alone were not enough to identify a tryptic peptide from a database unambiguously.…”
mentioning
confidence: 99%
“…The trend remains linear (Figure 5) but not perfectly scattered along the y = x line. The deviation originates from the inclusion of peptides with lower identification scores, as well as from identifications based only on one occurrence, which, by proteomic standards, 42 could mean that they are not present in the sample.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The results from these analyses, (a) 83 peptides of eight-model proteins, and (b) 102 peptides of Bacillus subtilis proteomes, were used for QSRR model development. Performed RP-LC-MS/MS analyses are described in detail by Macur et al …”
Section: Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The growth conditions of Bacillus subtilis strains 168 and ΔprpE , spore purification and protein extraction procedures were as previously described [ 33 ]. After that, the samples were treated according to the below presented digestion protocol.…”
Section: Methodsmentioning
confidence: 99%